A rare case of neurocutaneous disorders of the newborn: Incontinentia pigmenti - Melek Aslan Kayiran; Mehmet Salih Gürel; Burçe Can Kuru; Ilkin Zindancı (Wolters Kluwer Medknow Publications, 2018)
Incontinentia Pigmenti (IP) is a rare X-linked dominant disorder which is mostly lethal for males. It effects hair, teeth, nails, eyes and central nervous system along with skin. A twelve day old female patient was referred to the dermatology departmant due to skin eruptions that began the day before. There was a widespread erythema and many papuls and vesicles were seen on the eryhematous skin in linear sequence. Spongiosis with eosinophilia and necrotic keratinocytes were seen on histopathologic examination. The patient was diagnosed with incontinentia pigmenti. Vesicles and bullous eruption are rarely seen in newborns. The physcians should not avoid histopathologic examination especially in females. Since incontinentia pigmenti is a rare but multisystemic disorder, early diagnosis is crucial.